2017
DOI: 10.1038/s41598-017-05102-9
|View full text |Cite|
|
Sign up to set email alerts
|

Directional Exosome Proteomes Reflect Polarity-Specific Functions in Retinal Pigmented Epithelium Monolayers

Abstract: The retinal pigmented epithelium (RPE) forms the outer blood-retinal barrier in the eye and its polarity is responsible for directional secretion and uptake of proteins, lipoprotein particles and extracellular vesicles (EVs). Such a secretional division dictates directed interactions between the systemic circulation (basolateral) and the retina (apical). Our goal is to define the polarized proteomes and physical characteristics of EVs released from the RPE. Primary cultures of porcine RPE cells were differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 63 publications
5
108
1
Order By: Relevance
“…PCP provides a powerful approach to both identify bona fide resident proteins and to exclude contaminating proteins from a proteome dataset. We found that the vast majority of RPE-derived exosomal proteins that were highly co-enriched with the exosome-specific marker Syntenin-1 differed between the apical and basolateral side (Klingeborn et al, 2017), (Fig. 5), which was not unexpected if exosomes contribute to different apical versus basolateral signaling and pathways in these polarized cells.…”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 70%
See 4 more Smart Citations
“…PCP provides a powerful approach to both identify bona fide resident proteins and to exclude contaminating proteins from a proteome dataset. We found that the vast majority of RPE-derived exosomal proteins that were highly co-enriched with the exosome-specific marker Syntenin-1 differed between the apical and basolateral side (Klingeborn et al, 2017), (Fig. 5), which was not unexpected if exosomes contribute to different apical versus basolateral signaling and pathways in these polarized cells.…”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 70%
“…Supporting this notion, we recently identified A Disintegrin and Metalloproteinase Domain-Containing Protein 10 , also known as ADAM10, as a major component in highly purified exosomes released basolaterally from polarized RPE cultures (Klingeborn et al, 2017). Members of the ADAM family are transmembrane proteinases with a unique structure possessing both adhesion and catalytic domains.…”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 91%
See 3 more Smart Citations